A Theoretical Review of the Cognitive School and the Learning School in Strategic Education - Artati, Artati; Tampubolon, Manahan P; Murniarti, Erni; Limbong, Mesta (Jurnal Ilmiah Global Education, 2025)
The cognitive school emphasizes the importance of reasoning and interpretations in strategic actions by focusing on how people process information, create knowledge, and make decisions. On the other hand, the learning school places strong emphasis on organizational learning, viewing it as a living, breathing entity that continuously adapts to its environment. This article examines the core ideas of both approaches and assesses their relevance to management practices. It aims to provide deep insights into how strategies can be developed and implemented more successfully by integrating theories and models from both cognitive school and learning school. The article offers practical guidance for enhancing organizational performance and gaining competitive advantages in the fast-paced business environment through a literature review. Based on research findings, it can be concluded that both cognitive school and learning school can lead to successful outcomes through strategic processes and development.